2018
DOI: 10.1097/cad.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anticancer effect of MAP30–S3 by cyclosproin A through endosomal escape

Abstract: Cyclosporin A (CsA) is a calcium antagonist and can enhance the efficacy of some protein drugs, but its mechanism remains unknown. In this study, MAP30, a ribosome-inactivating protein reported to have apoptotic effects on cancer cells, was fused with S3, an epidermal growth factor receptor (EGFR)-targeting peptide. In addition, CsA was used to investigate whether it can further promote the apoptotic effects of S3 fused MAP30 (MAP30-S3). Our result showed that the internalization of FITC-labeled MAP30-S3 was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In addition, CQ also augmented the cytotoxicity of gelonin, granzyme B, and saporin by 3–15 times . Our previous work provided evidence for the EEE activity of cyclosporin A whereby the enhanced anticancer effect of MAP30-S3 was obtained with its cytosolic release as deduced from its diffused distribution in the cytoplasm …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, CQ also augmented the cytotoxicity of gelonin, granzyme B, and saporin by 3–15 times . Our previous work provided evidence for the EEE activity of cyclosporin A whereby the enhanced anticancer effect of MAP30-S3 was obtained with its cytosolic release as deduced from its diffused distribution in the cytoplasm …”
Section: Introductionmentioning
confidence: 75%
“…21 Our previous work provided evidence for the EEE activity of cyclosporin A whereby the enhanced anticancer effect of MAP30-S3 was obtained with its cytosolic release as deduced from its diffused distribution in the cytoplasm. 22 Of the structurally different EEEs, coadministration of a special class of EEEs comprising plant-derived glycosylated triterpenoids has been found to improve the pharmacological effects of protein drugs by more than 10 000 folds. 23 Glycosylated triterpenoids are a class of saponins comprising a triterpene aglycone to which one or more sugar moieties are attached, giving rise to a diversity of structural variations (reviewed in 24).…”
Section: Introductionmentioning
confidence: 99%
“…Other type 1 RIPs, such as Fordin (Lu et al, 2018), MAP30 (Lv et al, 2015) and Trichosanthin (Lin et al, 2017), showed moderate cytotoxicity with higher IC 50 values than OsRIP1. When MAP30 and Trichosanthin were fused to a penetrating peptide (HBD or S3) to enhance uptake in the cell, they were still less toxic for HeLa cells compared to recombinant OsRIP1 (Supplementary Table S6) (Lin et al, 2017;Lv et al, 2015;Song et al, 2018). It is widely accepted that type 2 RIPs are relatively more toxic than type 1 RIPs, due to the presence of a lectin chain which can bind to galactose residues on cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…116 One approach to facilitate and enhance the cytosolic delivery of ITs is the combination treatment with endosomal escape enhancers, such as chemicals, peptides, or proteins. 14,117,118 For instance, coadministration of bacterial pore-forming cytolysins and a gelonin-based IT, both of which have been designed to target the same antigen, potentiates the cytosolic delivery of gelonin by several orders of magnitude, resulting in a large increase in antitumor efficacy. 119 Chemical endosomal-escape enhancers, such as lysosomotropic amines and carboxylic ionophores, are membrane destabilizers (because they disrupt membrane integrity) or endosomolytic agents (because they inhibit the vesicular proton-ATPase pump) 14 ; therefore, they enhance the endosomal escape of coadministered ITs in in vitro settings.…”
Section: Cytosolic-delivery Efficacymentioning
confidence: 99%